Analysis Control of Spare Parts Inventory at PT XYZ In Gresik, East Java with ABC Analysis Method and EOQ Analysis Method - darno DARNO; khadijah binti Md ARIFFIN; Resista VIKALIANA; Eka SOFI; dewi agustya NINGRUM (Communications of International Proceedings, 2022)
Inventory is goods that will be used at a certain time which aims to avoid stockout or stagnation, so that demand and supply can be balanced. Inventory of spare parts is very important in the production process in addition to the inventory of raw materials because the operation of the company's machines depends on the spare parts inventory. This research was conducted to analyze the inventory of spare parts using the ABC analysis method and the EOQ method at PT. XYZ in Gresik, East Java. The result of this research is that there are 4 spare parts inventory items in group A with a cumulative percentage of 8.59% by absorbing a budget of 56.78%. There are 5 spare parts inventory items in group B with a cumulative percentage of 18.47% and absorbing a budget of 24.15%. In group C there are 17 spare parts inventory items with a cumulative percentage of 72.92% and absorbing a budget of 10%. In the EOQ method, The purchase quantity of 7 '' / 180X3X22 cut grinding stone spare parts of 196 with a purchase frequency of 7 times, the 4 / 100X6X16 sliding grinding stone of 130 with a purchase frequency of 6 times, a cloth mask of 434 with a purchase frequency of 11 times, cloth gloves of 411 with a purchase frequency of 11 times.
Keywords: inventory control; ABC analysis method; EOQ method.